2018
DOI: 10.1073/pnas.1711155115
|View full text |Cite
|
Sign up to set email alerts
|

BET bromodomain proteins regulate enhancer function during adipogenesis

Abstract: Developmental transitions are guided by master regulatory transcription factors. During adipogenesis, a transcriptional cascade culminates in the expression of PPARγ and C/EBPα, which orchestrate activation of the adipocyte gene expression program. However, the coactivators controlling PPARγ and C/EBPα expression are less well characterized. Here, we show the bromodomaincontaining protein, BRD4, regulates transcription of PPARγ and C/EBPα. Analysis of BRD4 chromatin occupancy reveals that induction of adipogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 36 publications
0
75
0
Order By: Relevance
“…To the best of our knowledge, the BRD4/CEBPD partnership was not previously recognized, likely due to a paucity of information on CEBPD in contrast to extensively studied CEBPA. A BRD4 functional association with CEBPA in adipogenesis was recently reported 28,30 , highlighting differential and contextual functions of different CEBP family members.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…To the best of our knowledge, the BRD4/CEBPD partnership was not previously recognized, likely due to a paucity of information on CEBPD in contrast to extensively studied CEBPA. A BRD4 functional association with CEBPA in adipogenesis was recently reported 28,30 , highlighting differential and contextual functions of different CEBP family members.…”
Section: Discussionmentioning
confidence: 91%
“…A unique interesting finding in this study is that CEBPD promotes its own transcription in SMCs, appearing to fit the concept of master TF. Among over a thousand TFs, a small number of socalled master TFs are critically important for cell identity, in other words, cell type or state 7,28,29 . Exemplary of master TFs, c-Myc is a powerful driver of oncogenic cell sate transitions 7 .…”
Section: Discussionmentioning
confidence: 99%
“…(30,31) SE activation alters the cellular transcriptome and can permit cell-state transition. (20,32) In the heart, this manifests as pathologic gene expression and the transdifferentiation of quiescent fibroblasts to myofibroblasts. (29) Precisely how this locus-specific flux of BRD4 to DCM-specific SEs occurs has not previously been elucidated in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…BETs inhibition was initially shown to be highly effective in blocking transcription programs of inflammation 28 and oncogenic proliferation 29 . The importance of BET biology was then extended to stem cell differentiation, hematopoiesis, synaptic plasticity 12 , and recently, also adipogenesis 10,30 . Most recently, BRD4 was found to regulate intra-nuclear/cellular processes as well, such as chromatin architectural remodeling 31 and autophagy 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, whether BETs are directly involved in cholesterol homeostasis remained unclear 12 . Relevant to this question, recent studies identified a crucial role of BRD4 in adipogenesis 10 . We were thus encouraged to explore whether BRD4 regulates the expression of S2R, a novel modulator of cholesterol transport 2 .…”
Section: Introductionmentioning
confidence: 99%